The COVID-19 pandemic and single-use plastic waste in households: a preliminary study - Leal Filho, Walter (2022)
The Coronavirus pandemic promoted an unprecedented change in consumption habits, especially as lockdowns contributed to the increase in online shopping and in delivery services. One of the consequences is the substantial amounts of plastic waste produced, which can undermine the efforts to reduce plastic pollution. In this context, this commentary explores, as a preliminary study, the impacts of the Coronavirus pandemic in relation to singleuse plastic waste in households by means of an international survey with 202 participants distributed over 41 countries worldwide.